PsycEXTRA Dataset 2014
DOI: 10.1037/e512142015-189
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences in opportunity cost consideration

Abstract: Two studies were conducted to investigate cultural differences in opportunity cost consideration between Chinese and Euro-Canadians. Opportunity cost is defined as the cost of a benefit that must be forgone in order to pursue a better alternative (Becker et al., 1974). In both studies, participants read about hypothetical purchase scenarios, and then decided whether they would buy a certain product. Opportunity cost consideration was measured in two ways: (1) participants' thoughts pertaining to other (nonfoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The next individual difference relates to cultural differences, as Zhang et al (2017) argued. Most of the research on opportunity cost consideration has been conducted in North America (e.g., Frederick et al, 2009;Northcraft & Neale, 1986;Spiller, 2011;Vera-Munoz, 1998), while the possibility of any differences between different regions is neglected.…”
Section: Culturementioning
confidence: 99%
See 3 more Smart Citations
“…The next individual difference relates to cultural differences, as Zhang et al (2017) argued. Most of the research on opportunity cost consideration has been conducted in North America (e.g., Frederick et al, 2009;Northcraft & Neale, 1986;Spiller, 2011;Vera-Munoz, 1998), while the possibility of any differences between different regions is neglected.…”
Section: Culturementioning
confidence: 99%
“…Similarly, Masuda and Nisbett (2001) found that, compared with Americans, Japanese people recall more information about contexts and relationships, and are more likely to recognize an object when it is presented in its original setting instead of a novel setting. Based on this information, Zhang et al (2017) argued that East Asians will consider opportunity costs more than Europeans and North Americans. Across two studies, they found that Chinese participants considered financial opportunity cost more than Europeans and Canadians did, despite controlling for other factors such as the amount of pocket money.…”
Section: Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Cost actualization is not only involved in company activities, but it is also related to the prevailed culture in a society (Zhang, 2013); (Tumirin dan A. Abdurahim, 2015), and (Rahmat, 2016), (Rahayu, S., 2016). Accounting, actually, created from local culture as form of culture where the accounting developed (Rahayu, S., 2015).…”
Section: Introductionmentioning
confidence: 99%